Genome‐Wide CRISPR‐Cas9 Screening Identifies NF‐κB/E2F6 Responsible for EGFRvIII‐Associated Temozolomide Resistance in Glioblastoma. Issue 17 (24th July 2019) - Huang, Kai; Liu, Xing; Li, Yansheng; Wang, Qixue; Zhou, Junhu; Wang, Yunfei; Dong, Feng; Yang, Chao; Sun, Zhiyan; Fang, Chuan; Liu, Chaoyong; Tan, Yanli; et al.
Abstract: Amplification of epidermal growth factor receptor (EGFR) and active mutant EGFRvIII occurs frequently in glioblastoma (GBM) and contributes to chemo/radio‐resistance in various cancers, especially in GBM. Elucidating the underlying molecular mechanism of temozolomide (TMZ) resistance in GBM could benefit cancer patients. A genome‐wide screening under a clustered regularly interspaced short palindromic repeats (CRISPR)‐Cas9 library is conducted to identify the genes that confer resistance to TMZ in EGFRvIII‐expressing GBM cells. Deep sgRNA sequencing reveals 191 candidate genes that are responsible for TMZ resistance in EGFRvIII‐expressing GBM cells. Notably, E2F6 is proven to drive a TMZ resistance, and E2F6 expression is controlled by the EGFRvIII/AKT/NF‐κB pathway. Furthermore, E2F6 is shown as a promising therapeutic target for TMZ resistance in orthotopic GBM cell line xenografts and GBM patient‐derived xenografts models. After integrating clinical data with paired primary–recurrent RNA sequencing data from 134 GBM patients who received TMZ treatment after surgery, it has been revealed that the E2F6 expression level is a predictive marker for TMZ response. Therefore, the inhibition of E2F6 is a promising strategy to conquer TMZ resistance in GBM. Abstract : A CRISPR‐Cas9 screening of temozolomide (TMZ) resistant glioblastoma cells is presented. NF‐κB is activated by TMZ treatment and EGFRvIII (epidermal growth factor receptor, EGFR) via PI3K/AKT, which leads to transcriptional induction of E2F6 expression. Cells with activated NF‐κB‐E2F6 survive under TMZ selection. TMZ withdrawal leads to cell proliferation and inhibition of NF‐κB/E2F6 prevents TMZ resistance.